Training on Making Water Hyacinth Compost to Increase Family Income in Gunong Pulo Village, West Aceh Regency: PELATIHAN PEMBUATAN KOMPOS ECENG GONDOK UNTUK PENINGKATAN PENDAPATAN KELUARGA DI DESA GUNONG PULO,KABUPATEN ACEH BARAT - Khairun Nisa; Liston Siringo Ringo; Teuku Athaillah; Dedy Darmansyah; Muhammad Reza Aulia; Abdul Muzammil; safrika; Fantashir Awwal Fuqara; Irvan Subandar; Munandar; Alfizar; Muhammad Sayuthi (WISDOM : Jurnal Pengabdian Kepada Masyarakat Wisdom, 2024)
Community economic empowerment through training in processing agricultural waste into compost organic fertilizer. With training in making compost, the aim is to increase farmers' independence and increase soil and plant fertility, thereby providing food diversification for family health and also improving the family economy. This training has great potential because most of the agricultural waste and water weeds, such as water hyacinth plants, are abundant in West Aceh Regency, especially in Arongan Lambalek District in Gunong Pulo Village. There has been an extraordinary increase in fertilizer prices, making it difficult for farmers to use fertilizers that can increase crop yields. Agricultural waste in West Aceh is very abundant, such as rice husks, rice straws, corn harvest residues, and other crops that are not used properly. Likewise, the water hyacinth weed is very disturbing to aquatic ecosystems, and the shallowing of water flows can be used as a basic ingredient for making compost fertilizer. Community service aims to utilize abundant agricultural waste for economic benefits, utilize abundant water weeds to reduce environmental damage, increase soil fertility and human health, and increase local economic independence. The service method consists of theory classes, practical demonstrations, and guided exercises in which participants are involved in guided exercises where they will try to directly make compost by working together to do the whole mixing, stirring, and chopping process. With this dedication, it is hoped that farmer groups will be able to produce vegetables again by making their organic water hyacinth compost fertilizer made from agricultural waste and water weeds.